The International Political Economy of Higher Education in the UK - Nora Ann, Colton (VNU Journal of Science: Social Sciences and Humanities, 2015)
The International Political Economy of Higher Education in the UK Deputy Vice Chancellor (Academic) and Professor Nora Ann Colton . There is no doubt that there is a correlation between the economic development of a country and its education (HE) system. It is less clear as to what the correlation is to economic growth and higher education (BIS 2013). Questions abound around variables, correlations and return. There are a number of unanswered questions in terms of the role higher education plays within the larger macro as well as micro economy of a state. In spite of these question marks, universities continue to be seen to generate innovation and ideas through research as well as training that prepares the labour force for employers.